Symbiodiniaceae density pattern in relation to colony morphology of scleractinian corals in Pulau Tioman and Pulau Bidong, Malaysia - Muhammad Arif Samshuri; Che Din Mohd Safuan; Nur Atiqah Maznan; Siti Nurtahirah Jaafar; Zainudin Bachok (Penerbit Universiti Kebangsaan Malaysia, 2023)
A healthy coral reef is linked to the mutualistic relationship between scleractinian coral and the symbiotic Symbiodiniacea (SD). However, there is limited research on SD in Malaysia, despite its important role in reef-building coral. In this study, the SD density of scleractinian corals from the family Acroporidae was evaluated to (i) examine the pattern of SD density and (ii) comprehend the regulation of the SD density by the host. The mean SD density ranged between 0.46 ± 0.01 × 106 cell cm-2 and 2.98 ± 1.17 × 106 cell cm-2. It is hypothetically proven that the SD density differed significantly between genera and morphological factors such as colony surface area (CSA) and dry weight coral tissue per unit colony surface area (DWCT/CSA) were significantly correlated with the SD density. The results show that the significant variation in SD density among coral genera can be influenced by coral growth forms and tissue biomass. There was a significant relationship between SD density and CSA as well as DWCT/CSA. Coral genera with a wider CSA and lower DWCT/CSA such as Anacropora and Acropora with branching, digitate and tabulate growth forms contained lower SD density than massive, laminar, and encrusting such as Montipora and Astreopora which hold more DWCT/CSA at lower CSA, resulting in higher SD density. The findings provide valuable information on SD density in different types of corals from the southern part of the South China Sea and reveal the coral host’s SD regulation.